Improvements in Math Instruction and Student Achievement Through Professional Learning Around the Common Core State Standards in Chicago - Elaine Allensworth; Sarah Cashdollar; Julia Gwynne (SAGE Publishing, 2021)
Existing literature on the impact of Common Core State Standards in Math has shown little benefit, but it has not examined variation in outcomes based on implementation strategies, student subgroups, or outcomes other than test scores. We use a difference-in-differences approach with school fixed effects to compare outcomes in pre- and poststandards years across schools with different levels of participation in professional learning around the standards in the middle grades in Chicago. Postimplementation, there were significantly greater improvements in student reports of standards-aligned instructional practices, math grades, pass rates, and test scores in schools with more extensive professional learning around the standards, among students with low and average initial achievement. Relationships were largely not significant for students with high initial achievement. We discuss why Chicago might have seen positive results, including the district emphasis on professional learning around the practice standards and differential impacts based on student prior achievement.